Central bank information effects and transatlantic spillovers - Marek Jarocinski (European Central Bank (ECB), 2020)
The news about the economy contained in a central bank announcement can affect public expectations. This paper shows, using both event studies and vector autoregressions, that such central bank information effects are an important channel of the transatlantic spillover of monetary policy. They account for a part of the co-movement of German and US government bond yields around Fed policy announcements, for most of this co-movement around ECB policy announcements, and significantly affect a range of financial and macroeconomic quantities on both sides of the Atlantic. These findings shed new light on the nature of central bank information.
Keywords: E52; F31; F42; 330; International Policy Transmission; Monetary Policy Shocks; HighFrequency Identification; Structural VAR